Histopathological changes and mRNA expression in lungs of horses after inhalation anaesthesia with different ventilation strategies. (August 2016) - Hopster, K.; Jacobson, B.; Hopster-Iversen, C.; Rohn, K.; Kästner, S.B.R.
Abstract: Inappropriate mechanical ventilation can lead to ventilator-induced lung injury (VILI). Aim of this study was to evaluate the effects of inhalation anaesthesia and ventilation with and without recruitment (RM) and PEEP titration on alveolar integrity in horses. Twenty-three horses were divided into 4 groups (group OLC ventilated with OLC, group IPPV ventilated with intermittent positive pressure ventilation, group NV non-ventilated, and group C non-anaesthetized control group). After sedation with xylazine and induction with diazepam and ketamine anaesthetized horses were under isoflurane anaesthesia for 5.5 h. The horses were euthanized and tissue samples of the dependent and non-dependent lung areas were collected. Histopathological examinations of the lung tissue as well as relative quantification of mRNA of IL-1β, IL-6, iNOS, MMP1 and MMP9 by PCR were performed. Horses of group OLC had significantly less alveolar congestion and atelectasis but greater alveolar overdistension compared to groups NV and IPPV. In groups OLC and group IPPV an increase in IL-1β/6 and MMP1/9 was detected compared to groups NV and C. In conclusion, in breathing spontaneously or IPPV-ventilated horses a higher degree of atelectasis was detected, whereas in OLC-ventilated horses a higher degree of overdistention was present. Elevated levels in IL and MMP might be early signs of VILI in ventilated horses. Highlights: In horses high respiratory pressures during alveolar recruitment cause only minor histological changes at the lungs Main effect is less atelectasis and minor alveolar overdistension without evident lung injury Overexpression of IL-1β/ ‐6 and MMP1/9 could be early signs of mild inflammation and overstretching of dependent alveoli